Dielectric investigations on metal (Ni and Cu) tetrahydroxy phenyl porphyrins in PMMA polymer matrix. (2022) - Prasanth, P.; Talam, Satyanarayana; Ramakrishna, Buthanapalli; Nagarjuna, Gunnam; Busi, Rambabu; Rao, M.C.; Nutalapati, Venkatramaiah
Highlights: Development metalloporphyrins doped PMMA polymer thin films. Study of dielectric parameters as function of temperature and frequency. CuTPPOH4 exhibits high conductivity while NiTPPOH4 show insulating behaviour. Variation of conductivity was studied by quantum tunnelling model. Abstract: The present work reports on the dielectric behaviour of two different metallo porphyrins (NiTPPOH4 and CuTPPOH4 ) doped in poly (methyl methacrylate) (PMMA) polymer matrix. Different dielectric parameters such as dielectric constant, tangent loss and a.c. conductivity were measured at frequency ranges from 1- 100 kHz in the temperature range 35–100 °C. The dielectric constant ε ' for NiTPPOH4 and CuTPPOH4 was found to be in the range of 2.42–5.45 and dielectric loss (tan δ) in the range of 0.0122–0.0756. The dielectric constant and loss are found to be higher for CuTPPOH4 . Variation in the dielectric loss with temperature at different frequencies show a shoulder peak indicating dipolar relaxation character. The a.c. conductivity of the materials increased with temperature and frequency. The activation energy was decreased with rise in temperature and shifting of relaxation regions towards low temperature is observed. Detailed analysis reveal that CuTPPOH4 doped polymer exhibit significant dielectric properties.